HADITH AND THE ETHICS OF PUBLIC SPACE: the Case of the Sea Fence Conflict in Tangerang - Saputra, Ilman Hendrawan (RIWAYAH, 2025)
The construction of a sea fence along the coast of Tangerang Regency has sparked complex legal, social, and religious controversies. This study critically examines the legal status of the project and its socio-economic implications for coastal communities through the lens of prophetic hadiths and Indonesian agrarian law. Employing a multidisciplinary methodology, the research integrates spatial analysis using historical Google Earth imagery (1985–2024), linear regression modeling for shoreline change estimation, normative analysis of regulations such as Government Regulation No. 24/1997 and Ministry of Agrarian and Spatial Planning Regulation No. 17/2021, and a textual analysis of relevant ṣaḥīḥ hadiths. The findings reveal systemic administrative irregularities involving land document falsification and abuse of authority, which contravene both Indonesian law and prophetic ethical teachings. Key hadiths—such as "Whoever cheats is not one of us" (Muslim No. 102), the warning against untrustworthy leadership (Bukhari No. 7150), and severe eschatological consequences for land usurpation (Bukhari No. 2454)—underscore the moral gravity of such practices. Beyond legal transgressions, the sea fence has resulted in the marginalization of local fishermen, economic dispossession, and rising communal tensions. This study contributes to the scholarship on Islamic environmental ethics, legal anthropology, and hadith application in contemporary governance by demonstrating how prophetic teachings can serve as normative frameworks for assessing development policies and protecting vulnerable communities.[Pembangunan tanggul laut di pesisir Kabupaten Tangerang telah memicu kontroversi hukum, sosial, dan keagamaan yang kompleks. Studi ini secara kritis menelaah status hukum proyek tersebut serta implikasi sosial-ekonominya terhadap masyarakat pesisir melalui perspektif hadis Nabi dan hukum agraria Indonesia. Dengan menggunakan pendekatan multidisipliner, penelitian ini mengintegrasikan analisis spasial menggunakan citra historis Google Earth (1985–2024), pemodelan regresi linear untuk estimasi perubahan garis pantai, analisis normatif terhadap regulasi seperti PP No. 24 Tahun 1997 dan Permen ATR/BPN No. 17 Tahun 2021, serta telaah tekstual terhadap hadis-hadis ṣaḥīḥ yang relevan. Temuan menunjukkan adanya penyimpangan administratif sistemik berupa pemalsuan dokumen tanah dan penyalahgunaan kewenangan, yang melanggar hukum positif maupun nilai-nilai etika kenabian. Hadis-hadis kunci—seperti “Barang siapa menipu, maka ia bukan dari golonganku” (HR Muslim No. 102), peringatan terhadap pemimpin yang tidak amanah (HR Bukhari No. 7150), serta ancaman keras terhadap perampas tanah (HR Bukhari No. 2454)—menegaskan beratnya pelanggaran moral tersebut. Di luar aspek hukum, pembangunan tanggul laut ini telah menyebabkan marjinalisasi nelayan lokal, kerugian ekonomi, dan meningkatnya konflik horizontal. Studi ini memberikan kontribusi terhadap kajian etika lingkungan Islam, antropologi hukum, dan penerapan hadis dalam kebijakan kontemporer, dengan menunjukkan bagaimana ajaran Nabi dapat menjadi kerangka normatif dalam menilai proyek pembangunan serta melindungi komunitas yang rentan.]